2000
DOI: 10.1038/35012103
|View full text |Cite
|
Sign up to set email alerts
|

B and C floral organ identity functions require SEPALLATA MADS-box genes

Abstract: Abnormal flowers have been recognized for thousands of years, but only in the past decade have the mysteries of flower development begun to unfold. Among these mysteries is the differentiation of four distinct organ types (sepals, petals, stamens and carpels), each of which may be a modified leaf. A landmark accomplishment in plant developmental biology is the ABC model of flower organ identity. This simple model provides a conceptual framework for explaining how the individual and combined activities of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
1,143
1
24

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 1,305 publications
(1,195 citation statements)
references
References 30 publications
27
1,143
1
24
Order By: Relevance
“…Using the yeast two-hybrid assay, we found that AP1 and CAL can each interact with a shared set of proteins, including SEP3, SOC1, SVP and AGL24. Thē ower-development roles of SEP3, SOC1 and SVP have all been recently documented (Hartman et al, 2000;Pelaz et al, 2000;Samach et al, 2000), whereas the function of AGL24 has yet to be determined. Given the fact that only one or a few clones were isolated for some of the genes in the yeast screens, it is likely that not all of the interacting factors have been identi®ed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the yeast two-hybrid assay, we found that AP1 and CAL can each interact with a shared set of proteins, including SEP3, SOC1, SVP and AGL24. Thē ower-development roles of SEP3, SOC1 and SVP have all been recently documented (Hartman et al, 2000;Pelaz et al, 2000;Samach et al, 2000), whereas the function of AGL24 has yet to be determined. Given the fact that only one or a few clones were isolated for some of the genes in the yeast screens, it is likely that not all of the interacting factors have been identi®ed.…”
Section: Discussionmentioning
confidence: 99%
“…If some of the activities of AP1 require an interaction with SEP3, then mutations in SEP3 might be expected to resemble mutant alleles of AP1. We recently identi®ed two independently derived En-1 transposon insertion alleles of SEP3, and have described the phenotype of sep1 sep2 sep3 triple mutants in which the three inner whorls of organs become sepaloid (Pelaz et al, 2000).…”
Section: Sep3 Mutants Resemble Intermediate Alleles Of Ap1mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, Blanc and Wolfe (2004b) and Maere et al (2005) show duplicate genes that constitute subunits of protein complexes are retained at a higher rate than other functional classes of genes, possibly due to stoichiometric requirements or dominant negative phenotypes following loss of one copy (Veitia 2003). AP3/DEF constitutes one subunit of a multidomain protein (Pelaz et al 2000) and thus might be disproportionately affected by such dosage effects. However, because these hypotheses predict retention of paralogs in an undifferentiated state and we see divergence between functional domains of DEFA/B, it is unlikely that they have contributed significantly to their preservation in Lamiales.…”
Section: Mechanisms Of Duplicate Gene Preservationmentioning
confidence: 99%